PENGEMBANGAN MEDIA PEMBELAJARAN MIND MAPPING DIGITAL INTERAKTIF BERBASIS MEANINGFUL LEARNING PADA MATERI PERAWATAN KULIT WAJAH SECARA MANUAL - Nurfika Aszka; Sri Usodoningtyas; Sri Dwiyanti; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2026)
Advancements in science and technology can be leveraged to develop interactive multimedia for instruction, thereby enhancing the quality of the teaching and learning process. This study aims to develop the media, assess its feasibility, analyze student learning outcomes, and identify student responses to the use of interactive digital mind-mapping media—grounded in the principles of meaningful learning—for the topic of manual facial skin care. The study employs the Research and Development (R&D) method. The product development process follows the 4D model, comprising the define, design, develop, and disseminate stages. The research was conducted at SMK Negeri 2 Ponorogo, specifically involving 31 students from class XC3. Data collection utilized questionnaires to assess media feasibility and student responses, cognitive learning outcome tests, and documentation. The results indicate that the interactive digital mind-mapping media was successfully developed in accordance with the 4D model stages and was rated as